Hydrologic analysis of a tropical watershed using KINEROS2 - Memarian, Hadi; Balasundram, Siva K.; Talib, Jamal; Teh, Christopher Boon Sung; Mohd Sood, Alias; Abbaspour, Karim C.; Haghizadeh, Ali (Thai Society of Higher Education Institutes on Environment, 2012)
The application of an event based physical model, KINEROS2, on a developed tropical watershed in Malaysia was evaluated. Three storm events in different intensities and durations were required for KINEROS2 (K2) calibration. K2 validation was done using two other rainfall events before and after the calibration year. Calibration results showed excellent and very good fittings for runoff and sediment simulations based on the aggregated measure. Validation results demonstrated that the K2 was reliable for runoff modelling while the K2 application for sediment simulation was only valid for the period 1984-1997.